Death and the American South - Friend, Craig Thompson; Glover, Lorri, 1967- (Cambridge studies on the American South., 2014)
"This rich collection of original essays illuminates the causes and consequences of the South's defining experiences with death. Employing a wide range of perspectives, while concentrating on discrete episodes in the region's past, the authors explore topics from the seventeenth century to the present, from the death traps that emerged during colonization to the bloody backlash against emancipation and civil rights to recent canny efforts to commemorate - and capitalize on - the region's deadly past. Some authors capture their subjects in the most intimate of moments: killing and dying, grieving and remembering, and believing and despairing. Others uncover the intentional efforts of Southerners to publicly commemorate their losses through death rituals and memorialization campaigns. Together, these poignantly told Southern stories reveal profound truths about the past of a region marked by death and unable, perhaps unwilling, to escape the ghosts of its history. Craig Thompson Friend is Professor of History and Director of Public History at North Carolina State University. Lorri Glover is the John Francis Bannon Endowed Chair in the department of history at St. Louis University"--